Prevalence and risk factors of osteoporosis among women aged 35 to 65 in Da Lat City, Lam Dong province - Trung, Dao Thanh; Nhut, Do Phu; Loc, Chau Viet; Nhan, Nguyen Thi Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Osteoporosis is a progressive condition characterized by decreased bone mineral density (BMD), leading to increased bone fragility and fracture risk. This study aimed to assess the prevalence of osteoporosis and identify associated risk factors among women aged 35 to 65 in Da Lat City, Lam Dong Province. Methods: A cross-sectional descriptive study was conducted on 497 women who had resided in Da Lat for at least three years. Osteoporosis was diagnosed based on BMD measurements, using the T-score criteria of the World Health Organization (WHO) for women aged 50 and older and the Z-score criteria of the International Society for Clinical Densitometry (ISCD) for those under 50. Results: The prevalence of osteoporosis was 5.8% at the femoral neck and 4.0% at the lumbar spine. Multivariate analysis identified two significant risk factors: inadequate physical activity (OR = 2.68; 95% CI: 1.08–6.65; p = 0.033) and overweight-obesity (OR = 3.61; 95% CI: 1.38–9.46; p = 0.009). Conclusion: The study highlights the need for increased public health efforts to promote physical activity and weight management as key strategies for osteoporosis prevention. Raising awareness and encouraging lifestyle modifications could help reduce the risk and burden of osteoporosis among women in this age group.